Effect of divalent metal ions on the viscosity of natural rubber from Manihot glaziovii - Rodrigues J F; Lima M C P; Oliveira F C; Ricardo N M P S (Journal of Rubber Research, 1998)
The effect of divalent metal ions on the intrinsic viscosity of natural rubber (NR) from Manihot glaziovii has been investigated. The molar mass of cis-1,4-polyisoprene from Manihot rubber was found to be Mv = 1.0 x 10 6 and the intrinsic viscosity [n] = 5.66 dL/g, for toluene solution at 30 degree C. some metal ions such a Ca 2= and Sr 2+ increase the NR viscosity in toluene solution (6.00 dL/g and 6.26 dL/g for 15.0 Mewmol of metal ion/g of rubber, respectively, for the same addition of metal ion/g of rubber. A correlation between relative variation of intrinsic viscosity ([n]NR+M/[n]NR) and cation radius has been proposed. A relative variation greater than unity for large cations has been observed, while for small metals such variation was less than 1. Cations that decrease the intrinsic viscosity do not lead to alteration in the activation energy of flow (Ea) for the 0.5;(w/v)(Ea =7.3kJ/mol) solution. Cations that increase [n] also cause an increase of Ea to 7.8 kJ/mol and 7.6 kJ/mol for NR solutions containing Sr2+ and Ca2+, respectively. Intramolecular crosslinks may be formed with small and large catioins. No evident interaction has been detected between metal ions and synthetic cis-1-4-polyisoprene. The interaction between NR and metal ions may be due to naturally occurring non-rubber constituents, probably those containing carboxylic groups.